Stem-Loop III in the 5′ Untranslated Region Is a cis-Acting Element in Bovine Coronavirus Defective Interfering RNA Replication - Raman, Sharmila (American Society for Microbiology, 2003)
Higher-order structures in the 5′ untranslated region (UTR) of plus-strand RNA viruses are known in many cases to function as cis-acting elements in RNA translation, replication, or transcription. Here we describe evidence supporting the structure and a cis-acting function in defective interfering (DI) RNA replication of stem-loop III, the third of four predicted higher-order structures mapping within the 210-nucleotide (nt) 5′ UTR of the 32-kb bovine coronavirus (BCoV) genome. Stem-loop III maps at nt 97 through 116, has a calculated free energy of −9.1 kcal/mol in the positive strand and −3.0 kcal/mol in the negative strand, and has associated with it beginning at nt 100 an open reading frame (ORF) potentially encoding an 8-amino-acid peptide. Stem-loop III is presumed to function in the positive strand, but its strand of action has not been established. Stem-loop III (i) shows phylogenetic conservation among group 2 coronaviruses and appears to have a homolog in coronavirus groups 1 and 3, (ii) has in all coronaviruses for which sequence is known a closely associated short, AUG-initiated intra-5′ UTR ORF, (iii) is supported by enzyme structure-probing evidence in BCoV RNA, (iv) must maintain stem integrity for DI RNA replication in BCoV DI RNA, and (v) shows a positive correlation between maintenance of the short ORF and maximal DI RNA accumulation in BCoV DI RNA. These results indicate that stem-loop III in the BCoV 5′ UTR is a cis-acting element for DI RNA replication and that its associated intra-5′ UTR ORF may function to enhance replication. It is postulated that these two elements function similarly in the virus genome.